Phylogenetic Analysis Revealed the Dissemination of Closely Related Epidemic Vibrio cholerae O1 Isolates in Laos, Thailand, and Vietnam. (16th October 2020) - Morita, Masatomo; Okada, Kazuhisa; Yamashiro, Tetsu; Sekizuka, Tsuyoshi; Roobthaisong, Amonrattana; Wongboot, Warawan; Chantaroj, Siriporn; Tu, Nguyen Dong; Xangsayarath, Phonepadith; Sithivong, Noikaseumsy; Noilath, Khambai; Vongdouangchanh, Arounnapha; et al.
Abstract: We performed whole-genome sequencing of Vibrio cholerae O1 isolates from Laos, Thailand, and Vietnam, where cholera outbreaks occurred, to determine their genetic lineages. Core genome phylogenetic analysis revealed that the isolates located in same lineage without regional clusters, which suggests that closely related strains circulated in Southeast Asia. Abstract : We performed whole-genome sequencing of Vibrio cholerae O1 isolates from Laos, Thailand, and Vietnam, where cholera outbreaks occurred, to determine their genetic lineages. Core genome phylogenetic analysis revealed that the isolates located in same lineage without regional clusters, which suggests that closely related strains circulated in Southeast Asia.